Systematic review: caspase-cleaved fragments of cytokeratin 18-the promises and challenges of a biomarker for chronic liver disease - YILMAZ, YUSUF (WILEY-BLACKWELL PUBLISHING, INC, 2009)
P>Background Biomarkers hold great promise for detecting chronic liver disease without the use of liver biopsy. Aim To review the usefulness of cytokeratin (CK) 18 fragments, a marker of hepatocyte apoptosis, to predict the presence of chronic liver injury. Methods Available literature identified from PubMed was reviewed. Results Levels of CK18 fragments have been shown to be elevated in hepatocellular carcinoma, viral hepatitis, alcoholic hepatitis, nonalcoholic fatty liver disease and cholestatic liver disease. In the setting of nonalcoholic fatty liver disease, CK18 fragments may distinguish nonalcoholic steatohepatitis from simple fatty liver. Conclusions Undoubtedly, the most promising application of CK18 fragments is currently in nonalcoholic fatty liver disease, and especially for distinguishing patients with nonalcoholic steatohepatitis vs. those with simple steatosis. Further investigations and technical improvements are required to cross the boundary from research to the clinical application of CK18 fragments as a marker of chronic liver disease.
Keywords: POLYPEPTIDE-SPECIFIC ANTIGEN; NONALCOHOLIC STEATOHEPATITIS; SERUM-LEVELS; EXTRACELLULAR CYTOKERATIN-18; INTERMEDIATE-FILAMENTS; HEPATOCYTE APOPTOSIS; CELL APOPTOSIS; SOLUBLE FORMS; HEPATITIS-C; INJURY